My Path from Chemistry to Phytochrome and Circadian Rhythms - Tobin, Elaine M. (Frontiers in Plant Science, 2016)
I summarize my scientific journey from my first interest in science to my career investigating how plants use the phytochrome photoreceptor to regulate what genes they express. I then describe how this work led to an understanding of how circadian rhythms function in plants and to the discovery of CCA1, a component of the plant central oscillator.